Industrial training report: Air Kelantan Sdn. Bhd. (Kelantan) / Muhammad Aziem Muhamad Saberi - Muhamad Saberi, Muhammad Aziem (Perpustakaan Tengku Anis, 2017)
Industrial Training is based on the period from O 1 August 2017 to 31 December 2017 at the Unit Pengurusan Jajahan at Air Kelantan Sdn. Bhd., Wisma Air Kelantan. Industrial training is aimed at giving experience the real work environment in the industry. Within five (5) months for students completing practical training in the Unit Pengurusan Jajahan it gives a lot of experience and knowledge to trainees to make them more responsible in doing things. In this unit it is responsible for administering and managing Headquarters level operations involving Districts Management and it is also responsible and ensures that every service and water supply system runs smoothly. Most of the work provided is related to the document and also collects data from the system. The system used to collect data is Sistem Pengebilan Air Kelantan (SISPAK.). In the industry training report it consists of 4 chapters, beginning with the introduction that chapter 1 consists of organizational background, unit information chapter 2 consists of unit function and structure, industrial training activities are included in chapter 3 and it is based on daily activities and a special project, and lastly, chapter 4, the conclusion of the entire chapter acquired during the fivemonth (5) month industry training.